Research Framework for Safety Culture in Malaysian Education Sector: Moderating Effect of Safety Knowledge - Kamilah Makhtar, Nor; Parasuraman, Balakrishnan; Nazri Zakaria, Mohd; Rasdan Ismail, Ahmad; Husna Che Hassan, Nurul (International Journal of Engineering and Technology, 2018)
The main purpose of the conceptual paper is to discuss development of a proposed conceptual framework in exploring the relationship between psychological, behaviour and situational dimension towards safety culture in Malaysian education sector focusly in Vocational College (VC). Previous literature showed fewer frameworks that have been established in occupational sector. A quantitative method was adopted, in which sample for the study was limited to vocational instructors that only teach enginering technology courses. The paper discusses possible relationship between all three dimensions with safety culture and offers a conceptual framework based on Cooperâ€™s Reciprocal Safety Cuture Model. Additional research is needed to empirically validate the proposed conceptual framework in the other organisation under education sector in Malaysia such as primary and secondary school, boarding school and also Matriculation College. This paper could assist top management and teachers in school to have deeper understanding of the importance of creating a positive safety culture at the workplace. The proposed conceptual framework could be used as a leading indicator for future research in this area especially in education sector.Â Â Â